Geopolitical concepts and thoughts of the Kazakh leaders and a new approach to their study (International relations and international law Journal, 2021)
Since the formation of the common concept of the international relations theory, it has undergone a lot of changes embarking on the path of development. A variety of opinions have been discussed in the scientific community concerning the fact that the international relations theory was shaped “in the West” and there is no analogous theory “in the East”. But the scholars of the Orient have developed new concepts, scientific ideas be studying thoroughly their history such as “international relations theory with the Chinese specific”. Chinese scholars have proved to their western counterparts that there exits an international relations theory in the East (namely in China).How can it be so that the Kazakh statehood deeply rooted in the past and having created dozens of Empires and Kaganates in the world arena, over a long period of international relations from ancient times to the present days could not have the theoretical basis of the geopolitical concepts and thoughts on the state structure and international rules? It is one of the main reasons that this article focuses on the search for the theoretical basis of the Kazakh leaders.The conquest of the cities along the Syr-Darya river by Kasym Khan, the legal basis of “Kazka jol” (Shining Path), the idea of integration of “Alty Alash” launched from the time of the Khans of Hacknazar and Tauekel and advanced by Abylai Khan and being the principal goals of Alash Orda, must become the major basis of foreign political concepts if Independent Kazakhstan.Key words: geopolitics, geopolitical ideas, “Alty Alash”, Kazakh leaders, integration.